The Romantic Imagination and Astronomy - Brothers, Dometa Wiegand. author. aut Link
X, 203 p.
Keywords: In the nineteenth century the beauty of the night sky is the source of both imaginative wonder in poetry and political and commercial power through navigation. The Romantic Imagination and Astronomy examines the impact of astronomical discovery and imperial exploration on poets including Barbauld, Coleridge, Keats, Shelley, and Rossetti.